2020
DOI: 10.3389/fmicb.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course RNAseq Reveals Exserohilum turcicum Effectors and Pathogenicity Determinants

Abstract: Exserohilum turcicum (sexual stage Setosphaeria turcica) is the hemibiotrophic causal agent of northern leaf blight of maize and sorghum. This study aimed to identify the genes involved in host colonization during the biotrophic and necrotrophic phases of infection. It also aimed to identify race-specific differences in gene expression. RNAseq of maize seedlings inoculated with a race 13N or 23N E. turcicum isolate was conducted before inoculation and at 2, 5, 7, and 13 days post-inoculation (dpi). Biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 81 publications
2
29
0
Order By: Relevance
“…The increase in XPE and XCE from 3 to 6 dpi indicates that between these time points, the pathogen is releasing virulence effectors. Transcriptional profiles showed that Ecp6 and SIX13-like proteins, similar to the secreted xylem effectors of Fusarium oxysporum, were overexpressed at 5 and 7 dpi (Human et al, 2020), which correlates to our findings in the histological studies and indicates that virulence effectors are being released at the time point before symptom expression (5-7 dpi).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increase in XPE and XCE from 3 to 6 dpi indicates that between these time points, the pathogen is releasing virulence effectors. Transcriptional profiles showed that Ecp6 and SIX13-like proteins, similar to the secreted xylem effectors of Fusarium oxysporum, were overexpressed at 5 and 7 dpi (Human et al, 2020), which correlates to our findings in the histological studies and indicates that virulence effectors are being released at the time point before symptom expression (5-7 dpi).…”
Section: Discussionsupporting
confidence: 88%
“…xylem colonization started (Kotze et al, 2019). Moreover, gene effector candidates encoded a hybrid polyketide synthase:nonribosomal peptide synthetase (PKS:NRPS) (Wu et al, 2015), and virulence-associated peptidases leupeptin-inhibiting protein 1 fungalysin involved in the biosynthesis of secondary metabolites and cell wall degradation (Human et al, 2020). The increase in XPE and XCE from 3 to 6 dpi indicates that between these time points, the pathogen is releasing virulence effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Foliar symptoms are characterised by cigar-shaped lesions with pointed ends which are not constrained by vein margins, and therefore are wider and larger than GLS lesions. 16 The fungi causing GLS and NLB appear to exploit different ecological niches in maize leaves with C. zeina entering through stomata and proliferating between cells 17 , whereas E. turcicum colonises the xylem and uses this as a 'pathway' to move through the maize leaf 15 .…”
Section: Extensive Survey Work Has Shown No Evidencementioning
confidence: 99%
“…27 Indeed, KwaZulu-Natal had the worst drought in this season since 1921. 28 High humidity is required for optimal development of these diseases 12,16 , and therefore less disease is consistent with the drought season of 2015/2016. Furthermore, the 2014/2015 season was also subject to drought 28 , and therefore the ranking and significant disease differences between the seasons is consistent with rainfall levels.…”
Section: Survey Of Maize Foliar Diseasesmentioning
confidence: 99%
“…repeat-induced point mutation (RIP) 6,7 , as well as increased rates of chromosome structure rearrangement 8,9 and lateral gene transfer 10 . Consequently, fungal effectors are highly diverse in sequence and function, and much effector candidate discovery is performed using experimental techniques such as phenotype association and comparative genomics [11][12][13][14] , transcriptomics [15][16][17] , proteomics 18,19 and GWAS 20,21 . There are, however, some protein characteristics -i.e.…”
Section: Introductionmentioning
confidence: 99%